Defeito de desenvolvimento do esmalte dentário e cárie da primeira infância em crianças prematuras e com baixo peso ao nascer - Elisa Feuser de Arjona (2018)
The aim of this paired cross-sectional study was to assess the oral conditions found in a group of preterm and / or low birth weight infants and their association with socioeconomic factors, gestational health and postnatal factors and to compare the findings with a group of children born to term. The convenience sample consisted of a group of 42 premature and / or low birth weight children from 2 to 5 years of age, from (ACRIAR) of the Hospital das Clínicas of the Federal University of Minas Gerais, Belo Horizonte, Brazil (G1). And with another group of 42 children from 2 to 7 years old with normal weight and born at term from public schools in the city of Belo Horizonte (G2). The study was matched by sex and age, in a ratio of 1: 1. After the approval of the UFMG Ethics Committee in Human Research (COEP / UFMG) and the propercalibration of the researcher for the clinical examination, the main study was carried out. Early childhood caries was evaluated according to the dmft index (OMS, 2012) and the defect in enamel development by DDE index (FDI, 1992). The children were examined according to the scheduling and demand of the hospital. A questionnaire was administered to the mothers of the children included in the study and medical records were searched for data from the postnatal period. For the children of the G2 group, the data were collected through questionnaires answered by the mothers, in addition to clinical oralexamination. Data collection was performed by a single examiner, trained and calibrated. After the data collection, the data were analyzed through the SPSS program. For the bivariate analyzes, the chi-square test was used and the multivariate analysis was the Poisson regression. A significance level of 5% was adopted. Individuals in the G1 group had a significantly higher number of DDE teeth compared to individuals in the G2 group (p = 0.007). The variables independent prematurity, maternal schooling, hospitalization, incubator, intubation, medication, and complications at delivery presented a value of p <0.20 in association with the DDE dependent variable. After the multivariate analysis, the variables that maintained association with the development of tooth enamel development were hospitalization after birth [(PR = 6.45 (95% CI= 1.59-11.36)] and medication during this period [(PR = 4.67 (95% CI = 1.82- 11.90)]. Children born prematurely presented more DDE than those born at term. No differences were observed between the groups of children born premature and term for early childhood caries (p = 0.803).